A resilient and sustainable world: Contributions from cleaner production, circular economy, eco-innovation, responsible consumption, and cleaner waste systems. (15th January 2023) - Giannetti, Biagio F.; Diaz Lopez, Fernando J.; Liu, Gengyuan; Agostinho, F.; Sevegnani, Fabio; Almeida, Cecilia M.V.B.
Abstract: This VSI focuses on what cross-cutting insights might be gained from research to increase the energy/materials circularity and the contribution of eco-innovation, cleaner consumption, and waste management to produce a logical body of knowledge that may lead to increased resilience and a sustainable Planet. The articles' collection shows development trends of sustainable, cleaner production under the Special Issue: A Resilient and Sustainable World. Some selected d papers have been presented and emerged from the 10th and 11th International Workshop on Advances in Cleaner Production (IWACP), held in hybrid mode in Italy (Ferrata and Florence). The contribution of the articles in this Special Issue could be divided into efforts toward sustainable and cleaner production, aiming (i) Eco-innovation for cleaner production and circular economy, (ii) Proper monitoring and identification of cleaner production, circular economy, and eco-innovation, (iii) cleaner production, circular economy and eco-innovation targeting social wellbeing and cleaner environment, (iv) cleaner production, circular economy and eco-innovation targeting emission reduction, and (v) cleaner production, circular economy and eco-innovation targeting improved and optimized production processes.